Consumers' preferences for biodiversity in vineyards: A choice experiment on wine - Chiara Mazzocchi; Giordano Ruggeri; Stefano Corsi (Wine Economics and Policy, 2019)
In recent years consumers' concerns regarding the environmental impact of food production has significantly increased, also due to food sustainability, food safety and food security issues. A number of certification systems for environmental-friendly products have been created e.g. water-saving labels and fishery sustainable labels. Among various environmental issues, the protection of biodiversity has recently gained popularity both in public opinion and in scientific debate. This paper describes the results of a Choice Experiment on wine consumers to estimate their willingness to pay for biodiversity conservation practices in vineyards. The survey was conducted by direct interviews at a wine tasting event in an Italian winery located at Montefano (Marche). The results show that consumers are willing to pay a premium price for wine certification that takes into account biodiversity not only for medium-high price wines, but also for low-price wines. Finally, quality of wine and organic certification remain important attributes in wine purchasing choices related to expensive wines.
Keywords: 330